KONSELING SUPPORTIF BERBASIS ISLAMIDALAM MENINGKATKAN SELF ACCEPTANCE REMAJA DENGAN PROBLEM KECEMASAN - widya laksana, budiarda (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
Self-Accepatnce is a problem that often occurs in individuals who experience anxiety. Counseling is an alternative to help with anxiety problems. The aim of this research is to help increase self- acceptance which is characterized by the ability to accept everything that exist in oneself, both the weaknesses and strength that the research has. This is study uses a qualilatuive case study approach and uses a single subject design. The intervention provided is psychoanalytic counseling with supportive counseling techniques. The counseling that the subject participated in resulted in changes in the subject, there was a decrease in three criteria, the fisrt criterion was anxiety aboute the future, the subject became more optimistic about the future by making plans related to the future and a calmer mind, the second criterion was positive changes that the subject experienced, such as sleeping more quality, and can manage excessive anxiety and thirdly the subject feels more comfortable because he can express suppressed feelings and is able to express desires with more logical thougts.